INTRATHECAL ROUTE ROMIFIDINE, BUPIVACAINE, FENTANYL OR ASSOCIATIONS ADMINISTRATION FOR MONGREL DOGS PREMEDICATED WITH ACEPROMAZINE AND DIAZEPAN - FARIAS, Anderson (Scientia Agraria, 2000)
Alleviating pain in animals after accidental or surgical injury is a major concern of veterinary care providers. Epidural administration of analgesic agents has proven effective in management of somatosensory and visceral pain. The aim of this study was investigate six anesthetic protocols administered in spinal medulla by intrathecal route using six adult animals per group. T1: romifidine (60 µg/kg), T2: bupivacaine (1,0 mg/kg), T3: fentanyl (5,0 µg/kg), T4: bubivacaine + fentanyl (0,5 mg/kg + 2,5 µg/kg), T5: bupivacaine + romifidine (0,5 mg/kg + 30 µg/kg) e T6: romifidine + fentanyl (30 µg/kg + 2,5 µg/kg). These animals were premedicated with acepromazine (0,1 mg/kg) and diazepam (1,0 mg/kg) lV. Heart and respiratory rates, temperature, O2 saturation, systolic, mean and diastolic pressures, interdigital and anal reflexes, muscle relaxation and coetaneous sensibility were measured during anesthesia with 15 min of the interval during 110 min. The acepromazine and diazepam produced an excellent chemical restraint. The Romifidine produced isolated or in association, at spinal level, a potent antinociceptive effect, while your redistribution carried a hypnotic state with significative cardiorespiratory effects. Fact observed in treatment 5 (bupivacaine + romifidine) and treatment 6 (fentanyl + romifidine). The bupivacaine characterized by hypothermia and hipotension, with potent spinal blocked, and good muscle relaxation and longer analgesia duration. The fentanyl produced minimal cardiorespiratory alteration, with good analgesia of the short duration and no loss muscle tonus. The treatment 4 (bupivacaine + fentanyl) detached by excellent anesthetic pattern with minimal cardiorespiratory alteration.